Effect of childhood adversity on health related quality of life in patients with upper abdominal or chest pain. Issue 2 (14th January 2004) - Biggs, A-M; Aziz, Q; Tomenson, B; Creed, F
Abstract : Background and aims: This study assessed whether childhood and current adversities: (a) were more prevalent in patients with functional dyspepsia (FD) or non-cardiac chest pain (NCCP) than in patients with gastro-oesophageal reflux disease (GORD) or ischaemic heart disease (IHD); and (b) predicted health related quality of life in these disorders. Patients: Cohort study of consecutive attenders to gastroenterology and cardiology clinics in a secondary/tertiary referral centre. Methods: Patients were interviewed using the childhood experience of care and abuse and life events and difficulties schedules. Distress was assessed by questionnaire. Outcome was assessed using SF36 at the index clinic visit and six months later. Results: A total of 133 patients were included (40 NCCP, 43 FD, 29 GORD, and 21 IHD) (67% response rate). The diagnostic groups did not differ significantly in the proportion reporting childhood adversity (30%), ongoing social stress (40%), lack of a close confidant (14%), or level of psychological distress. Reported childhood adversity was associated with poor outcome at the index visit (SF36 physical component score: 36.6 (SEM 1.8) v 42.3 (SEM 1.2) for the remainder; p = 0.014). In multiple regression analysis, childhood adversity was a significant independent predictor for patients with functional disorders (NCCP and FD) but not organic disorders (GORD or IHD). Change in SF36 score at six months was determined by age and distress score at the index visit in both groups. Conclusion: Childhood adversity was common among this consecutive sample but was associated directly with poor outcome only in patients with functional gastrointestinal syndromes. Distress is an important predictor of outcome in all patients. Greatest impairment occurs when lack of social support accompanies reported childhood adversity.